The impact of preparatory activities on the largest clinical aptitude test for prospective medical students in Germany - Weppert, Daniel; Amelung, Dorothee; Escher, Malvin; Troll, Leander; Kadmon, Martina; Listunova, Lena; Montasser, Jana (Frontiers in Education, 2023)
Background: Aptitude tests are widely used for selecting medical students. Although their validity has been well documented, aptitude tests are sometimes suspected to create unequal opportunity for candidate groups with lower socioeconomic status due to limited resources (i.e. time, money, support) for preparatory activities. This study aims to explore how preparatory activities and money spent on preparation affect the results of the German aptitude Test for Medical Studies (TMS). Methods: A standardized questionnaire was administered to all medical school applicants who sat the TMS in 2018. Participants were asked about the amount of time and money spent on different preparatory activities (i.e. information booklet, books, computer, study groups, and fee-based training courses) and their level of motivation during preparation. Univariate and multivariate multiple regressions were used to examine the influence of these variables on the TMS test score and its subtests. Results: N = 7903 participants completed the questionnaire. Only preparation with books and training courses were significantly associated with an increase in the TMS total score. Self-reported motivation during preparation had a larger effect on test scores than money spent on preparation. However, all effect sizes were rather small. At the subtest level, preparation with books was the only activity which was significantly associated with an improvement in all subtests. The complex field-specific subtests were less associated with preparation than the less complex subtests. Conclusion: The findings indicate that motivation may be a more important predictor for success in the TMS than money spent on preparation. As books were the most effective and cost-efficient way of preparation, financial investments for test preparation do not appear to yield significant advantages, which is an important prerequisite for equal opportunity. Using more field-specific subtests and cost-free online training opportunities could be useful in further improving equal opportunity.